Characterization of the Silicon Uptake System and Molecular Mapping of the Silicon Transporter Gene in Rice - Ma, J.F.; Mitani, N.; Nagao, S.; Konishi, S.; Tamai, K.; Iwashita, T.; Yano, M.
Rice (Oryza sativa L. cv Oochikara)is a typical silicon-accumulating plant, but the mechanism responsible for the high silicon uptake by the roots is poorly understood. We characterized the silicon uptake system in rice roots by using a low-silicon rice mutant (lsi1)and wild-type rice. A kinetic study showed that the concentration of silicon in the root symplastic solution increased with increasing silicon concentrations in the external solution but saturated at a higher concentration in both lines. There were no differences in the silicon concentration of the symplastic solution between the wild-type rice and the mutant. The form of soluble silicon in the root, xylem, and leaf identified by 29Si-NMR was also the same in the two lines. However, the concentration of silicon in the xylem sap was much higher in the wild type than in the mutant. These results indicate that at least two transporters are involved in silicon transport from the external solution to the xylem and that the low-silicon rice mutant is defective in loading silicon into xylem rather than silicon uptake from external solution to cortical cells. To map the responsible gene, we performed a bulked segregant analysis by using both microsatellite and expressed sequence tag-based PCR markers. As a result, the gene was mapped to chromosome 2, flanked by microsatellite marker RM5303 and expressed sequence tag-based PCR marker E60168.